Effects of p38 mitogen-activated protein kinase inhibition on anti-neutrophil cytoplasmic autoantibody pathogenicity in vitro and in vivo. Issue 2 (9th November 2010) - van der Veen, Betty S; Chen, Min; Müller, Ralf; van Timmeren, Mirjan M; Petersen, Arjen H; Lee, Patrice A; Satchell, Simon C; Mathieson, Peter W; Saleem, Moin A; Stegeman, Coen A; Zwerina, Jochen; Molema, Grietje; et al.
Abstract : Objective: To determine whether inhibition of p38 mitogen-activated protein kinase (p38MAPK) reduces the pathogenicity of anti-neutrophil cytoplasmic autoantibodies (ANCAs) in vitro and in vivo. Methods: The effects of the p38MAPK-specific inhibitor AR-447 were studied in vitro using neutrophil respiratory burst and degranulation assays, and in lipopolysaccharide (LPS)-stimulated human glomerular endothelial cells. In vivo, p38MAPK inhibition was investigated in a mouse anti-myeloperoxidase (MPO) IgG/LPS glomerulonephritis model. Mice were treated orally with AR-447 daily, starting before (pretreatment group) or 24 h after disease onset (treatment group), and killed after 1 or 7 day(s). Results: In vitro, AR-447 diminished neutrophil respiratory burst and degranulation induced by patient-derived MPO-ANCA and proteinase 3 (Pr3)-ANCA. In glomerular endothelial cells, AR-447 reduced LPS-induced secretion of IL-6 and IL-8, but not of MCP-1. In mice, pretreatment with AR-447 reduced albuminuria 1 day after induction of glomerulonephritis. After 7 days, no effects on urinary abnormalities were observed upon AR-447 pretreatment or treatment. Also, glomerular neutrophil accumulation was not diminished. In contrast, glomerular macrophage accumulation and the formation of glomerular crescents was significantly reduced by AR-447 pretreatment (vehicle: 12.5 ± 5.6% crescentic glomeruli; AR-447: 7.7 ± 2.7%) and treatment (vehicle 14.6 ± 1.8%; AR-447 6.0 ± 3.4%) at 7 days. Conclusion: This study shows that p38MAPK inhibition markedly reduces ANCA-induced neutrophil activation in vitro. In vivo, p38MAPK inhibition partly reduced crescent formation when the drug was administered prior to disease induction and after disease onset, suggesting that besides p38MAPK activity other signalling pathways contribute to the disease activity.